ANALISIS DAN PERENCANGAN SISTEM INFORMASI MANAJEMEN CAFE BERBASIS ANDROID PADA CAFE KOPI PEDALAMAN - Kurniawan, Tomi; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2020)
Order list management is still processe manually which used the note and make some problem and effectedthe optimal of the cafe management. One of the way to manage and optimize the management in that cafewith using the informastion system. The study research of the cafe management will stresses in order side,stock, transaction and booking the result of the study/research was saw the prototype system who describethe fungsional of order, stock, transaction and booking order in cafe Kopi Pedalaman. The methos of thisstudy/research was use the objective orientation with UML (Unified Modelling Language) and using the casediagram, class diagram and activity diagram. This study/research produce/resulted the prototype might bemore implimented until itu could produced the system information of cade management who couldimplimented to cafe Kopi Pedalaman